Contemporary Japanese thought - Calichman, Richard (New York : Columbia University Press, 2005)
Appearing for the first time in English, the writings in this collection reflect some of the most innovative and influential work by Japanese intellectuals in recent years. The volume offers a rare and much-needed window into the crucial ideas and positions currently shaping Japanese thought (shiso). In addressing the political, historical, and cultural issues that have dominated Japanese society, these essays cross a range of disciplines, including literary theory, philosophy, history, gender studies, and cultural studies. Contributors examine Japan's imperialist and nationalist p.
The politics of teasing ; A feminist view of Maruyama Masao's modernity / Ehara Yumiko -- The imaginary geography of a nation and denationalized narrative ; The discovery of the "Orient" and Orientalism / Kang Sangjung -- Overcoming modernity ; Sōseki's diversity: on Kokoro / Karatani Kōjin -- The wonderland of "immortality" / Nishitani Osamu -- Two negations: the fear of being excluded and the logic of self-esteem / Naoki Sakai -- Japanese neo-nationalism: a critique of Katō Norihiro's "After the defeat" discourse ; From the Hinomaru and Kimagayo to the symbolic emperor system / Takahashi Tetsuya -- In the feminine guise: a trap of reverse Orientanlism ; Collapse of "Japanese mothers" / Ueno Chizuko -- Colonialism and modernity ; Reflections beyond the flag: Why is the Hinomaru flag "auspicious/foolish"? / Ukai Satoshi.
Includes bibliographical references and index.
Print version record.
In English.
JSTOR
Keywords: Japan -- Civilization -- 1945-; Japon -- Civilisation -- 1945-; HISTORY; HISTORY -- Asia -- Central Asia; Civilization; Japan; Since 1945